Wave run-up and response spectrum for wave scattering from a cylinder - Zang, J; Liu, S; Taylor, R; Taylor, P (2008)
In this paper, we present both numerical and experimental studies on non-linear wave interaction with a circular cylinder in shallow water and examine the effect of non-linearity on the wave run-up on the structure. Second order wave diffraction theory has been included in the numerical simulation to steep waves. Both the wave run-up time history on the cylinder and the wave response spectrum derived from the diffracted wave time series are investigated and compared with the experiments conducted in a wave tank. Numerical predictions from the second order diffraction simulations agree very well with the experimental measurements for both wave run-up and response spectrum. This validation confirmed that the second order wave diffraction solution works well for steep waves in shallow water, while linear diffraction theory incorrectly predicts the peak water levels and response spectrum. Copyright © 2008 by The International Society of Offshore and Polar Engineers (ISOPE).